1999
DOI: 10.1002/(sici)1097-0274(199903)35:3<257::aid-ajim5>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in semen quality associated with decreasing occupational lead exposure

Abstract: Background Cross‐sectional studies have suggested that occupational lead exposure may adversely affect sperm quality. >Methods Sperm quality changes were prospectively assessed in 19 men employed at a car battery plant where efforts were made to decrease the exposure level. The participants delivered monthly samples of semen and venous blood during their employment at the factory. The factory then closed, and additional samples were obtained from 16 of the men. Results Average blood‐lead concentrations decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…However, some studies have reported the possibility of adverse health effects even at lower PbB levels suggesting that there is no safe level of exposure (Canfield et al, 2003). Viskum et al (1999) reported that occupational lead exposure at acceptable levels has a small adverse effect on sperm quality, especially sperm motility. 20 lg dl À1 (n = 11), while no significant difference was reported as regards spermatic count and abnormal forms when compared with the group PbB 20 lg dl À1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported the possibility of adverse health effects even at lower PbB levels suggesting that there is no safe level of exposure (Canfield et al, 2003). Viskum et al (1999) reported that occupational lead exposure at acceptable levels has a small adverse effect on sperm quality, especially sperm motility. 20 lg dl À1 (n = 11), while no significant difference was reported as regards spermatic count and abnormal forms when compared with the group PbB 20 lg dl À1 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the findings in our study, a longitudinal study of Danish battery workers found no improvement of sperm concentration along with a decline in blood lead concentration from about 40 to 20 µg/dl. 6 From a comprehensive study in rabbits Moorman et al estimated a threshold for total sperm count of 23.7 µg/dl. 9 Taking random variation and noise in an epidemiological study into account this is not entirely different from the 44 µg/dl found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational activities involving exposure to specific chemicals or expositions to toxicants may impair male reproductive health and cause infertility in humans [27,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%